Pengaruh Pembelajaran Aktif Berbantuan Media Bonus (Boneka Nusantara) Terhadap Hasil Belajar IPS - Cahya, Yuka Rahmah Tiara (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the active learning model assisted by the BONUS (Boneka Nusantara) media on social studies learning outcomes for fourth grade students at SD N Sukorejo Magelang. This research is a type of experimental research with Pre-experimental research design with the "One Group Pretest-Posttest Design" model. The research subjects are 10 fourth grade students of SD N Sukorejo in Ganjuran Village which consists of 10 female students as the experimental class. The sampling technique used was saturated purposive sampling technique. The data collection technique used pretest and posttest questions regarding ethnic and cultural diversity and observation. Data analysis in this study was assisted by using SPSS version 25 to calculate the validity, reliability, discriminating power, and level of difficulty of the questions. Validity test using product moment correlation and instrument reliability using Cronboach's Alpha. The data analysis technique in this study uses the Kolmogorov- Smirnov analysis prerequisite test and the hypothesis test uses the Paired Sample T- Test. The results showed that the active learning model assisted by the Nusantara doll media had a positive effect on student learning outcomes. This is evidenced from the results of the analysis of the Paired Sample T-Test in the experimental group with a sig (2-tailed) value of 0.000 <0.05 and the result of tcount 7.488 > 2,228 ttable . Based on the results of the analysis and discussion, there is a difference in the pretest score of 60 and the posttest of 78. The results of the study can be concluded that the use of active learning aided by the Nusantara doll media has a positive effect on the learning outcomes of fourth grade students of SD N Sukorejo.